1999
DOI: 10.1177/002246699903300103
|View full text |Cite
|
Sign up to set email alerts
|

When Does Consultation Lead to Intervention Implementation?

Abstract: For consultation to result in the delivery of services to students, it must lead to implementation of an intervention. For this reason, intervention implementation is the crucial challenge for the practice of consultation and, as a result, is the critical research need. The argument is advanced that too little is known about the extent to which teachers actually implement interventions following consultation, as opposed to what they say about implementation, because implementation has infrequently been directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…In the case of the consultancy approach (McCartney et al, 2011), mainstream staff failed to implement the amount of language-learning activity required to adhere to the therapeutic program possibly because the staff simply did not have sufficient resources to manage the added demands of providing the intervention program. Indeed, there is evidence that SLP consultation may not necessarily lead to changed teacher behaviour (Noell & Witt, 1999), that teachers may not report benefiting from SLP consultations (Dockrell & Lindsay, 2001), and may have little access to SLPs for consultation (Baxter, Brookes, Bianchi, Rashid, & Hay, 2009). The bottom line is SLP-educator collaboration will be ineffectual (or nonexistent) if the partners lack the necessary time or other resources to implement services appropriately.…”
Section: The Challenge Of Changementioning
confidence: 99%
“…In the case of the consultancy approach (McCartney et al, 2011), mainstream staff failed to implement the amount of language-learning activity required to adhere to the therapeutic program possibly because the staff simply did not have sufficient resources to manage the added demands of providing the intervention program. Indeed, there is evidence that SLP consultation may not necessarily lead to changed teacher behaviour (Noell & Witt, 1999), that teachers may not report benefiting from SLP consultations (Dockrell & Lindsay, 2001), and may have little access to SLPs for consultation (Baxter, Brookes, Bianchi, Rashid, & Hay, 2009). The bottom line is SLP-educator collaboration will be ineffectual (or nonexistent) if the partners lack the necessary time or other resources to implement services appropriately.…”
Section: The Challenge Of Changementioning
confidence: 99%
“…Building leadership also affects the extent to which teachers use proven, research-based practices to improve student performance (Embich, 2001;Noell & Witt, 1999).…”
Section: The Principal's Role In Providing Effective Special Educatiomentioning
confidence: 99%
“…Moreover, they reported that they benefited from the program and would recommend it to other people. With all intervention research, it is important to examine the acceptability of the intervention, because adoption and effective implementation of an intervention involves more than whether an intervention will produce results (Noell & Witt, 1999). Moreover, interventions found to be acceptable may not actually be implemented with integrity (Sanetti & Kratochwill, 2009).…”
Section: Discussionmentioning
confidence: 99%